2001
DOI: 10.1164/ajrccm.163.7.2006077
|View full text |Cite
|
Sign up to set email alerts
|

Role of Molds in Farmer's Lung Disease in Eastern France

Abstract: Farmer's lung disease (FLD) is common in the east of France. In the absence of the primary recognized FLD agent, Saccharopolyspora rectivirgula, its etiology remains unknown. A prospective case-control study was performed to find the etiology of FLD in this area. Eleven patients were matched with 11 healthy control farmers. Twenty-two urban subjects constituted the nonexposed control group. Microorganisms from cowshed air and fodder were identified and counted. The antigens of the microorganisms most frequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(84 citation statements)
references
References 23 publications
2
79
1
2
Order By: Relevance
“…Among these criteria, serology has long been considered to be either a minor criterion or a simple marker of exposure [23][24][25][26]. However, with typical FL patients, the use of antigens isolated from patients' environments has lead to convincing results [11,27]. In addition, a recent study by LACASSE et al [4] identified serum precipitins as a significant predictive factor of HP, regardless of exposure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Among these criteria, serology has long been considered to be either a minor criterion or a simple marker of exposure [23][24][25][26]. However, with typical FL patients, the use of antigens isolated from patients' environments has lead to convincing results [11,27]. In addition, a recent study by LACASSE et al [4] identified serum precipitins as a significant predictive factor of HP, regardless of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…and hay extract. Antigen extracts were produced and tested as described in a previous article [11]. The immunological methods used were agar gel double diffusion and electrosyneresis on cellulose acetate, which, as shown by a recent study, are more relevant than ELISA and immunoblots in discriminating FL from healthy exposed dairy farmers in the present study's region [12].…”
Section: Precipitins Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…The selection of antigens to be tested often needs to be determined locally according to the prevalent antigens (4,51). In eastern France, by using a panel of antigens really responsible for farmerÕs lung and not a classical standardized panel, serological tests showed a high rate for sensitivity and specificity (52).…”
Section: Specific Antibodiesmentioning
confidence: 99%